Biochemical properties of VGLL4 from Homo sapiens and Tgi from Drosophila melanogaster and possible biological implications. (8th June 2021) - Mesrouze, Yannick; Meyerhofer, Marco; Zimmermann, Catherine; Fontana, Patrizia; Erdmann, Dirk; Chène, Patrick
Abstract: The TEAD (Sd in drosophila) transcription factors are essential for the Hippo pathway. Human VGLL4 and drosophila Tgi bind to TEAD/Sd via two distinct binding sites. These two regions are separated by few amino acids in VGLL4 but they are very distant from each other in Tgi. This difference prompted us to study whether it influences the interaction with TEAD4/Sd. We show that the full‐length VGLL4/Tgi proteins behave as intrinsically disordered proteins. They have a similar affinity for TEAD4/Sd revealing that the length of the region between the two binding sites has little effect on the interaction. One of their two binding sites (high‐affinity site) binds to TEAD4/Sd 100 times more tightly than to the other site, and size exclusion chromatography experiments reveal that VGLL4/Tgi only form trimeric complexes with TEAD4/Sd at high protein concentrations. In solution, therefore, VGLL4/Tgi may predominantly interact with TEAD4/Sd via their high‐affinity site to create dimeric complexes. In contrast, when TEAD4/Sd molecules are immobilized on sensor chips used in Surface Plasmon Resonance experiments, one VGLL4/Tgi molecule can bind simultaneously with an enhanced affinity to two immobilized molecules. This effect, due to a local increase in protein concentration triggered by the proximity of the immobilized TEAD4/Sd molecules, suggests that in vivo VGLL4/Tgi could bind with an enhanced affinity to two nearby TEAD/Sd molecules bound to DNA. The presence of two binding sites in VGLL4/Tgi might only be required for the function of these proteins when they interact with TEAD/Sd bound to DNA.